Entrepreneurship in a post-socialist country: a controversial influence on life-quality - Jucevicius R. (Selected readings on economies in transition, 2000)
Despite the dramatic changes in the whole post-socialist world, there are also certain obstacles in their way towards the free market. There existed only a few non-public enterprises such as those involved in the cultivation and selling of flowers. That certainly affected the mentality and life style of the people. Private entrepreneurial activity is an entirely new phenomena for these countries. The purpose of this paper is to analyse the role of entrepreneurship in the economic development of these countries and its effect on quality of life.